Environmental exposure of commuters in Mexico City to volatile organic compounds as assessed by blood concentrations, 1998 Exposición ambiental a compuestos orgánicos volátiles evaluados en concentraciones sanguíneas en usuarios de transporte en la Ciudad de México, 1998 - Sharon Lemire; David Ashley; Patricia Olaya; Isabelle Romieu; Susan Welch; Fernando Meneses-González; Mauricio Hernández-Avila (Instituto Nacional de Salud Pública, 2004)
OBJECTIVE: To assess the extent of exposure for Volatile Organic Compounds (VOCs) among nonoccupationally exposed commuters in Mexico City. MATERIAL AND METHODS: Blood concentrations of benzene, toluene, ethylbenzene, m-/p-xylene, o-xylene and methyl tert-butyl ether were determined on samples collected from participants after the morning commute. RESULTS: Median blood concentrations of benzene (0.11 mg/l), ethylbenzene (0.081 mg/l), m-/p-xylene (0.32 mg/l) and toluene (0.56 mg/l) in the Mexico City participants were all approximately two times higher than in a nonsmoking subset of the Third National Health and Nutrition Examination Survey population of the United States. On the other hand, median VOC blood levels were similar to medians observed in other studies involving commuters in specific U.S. cities, despite the fact that only half the Mexico City study participants commuted by personal vehicles compared with all U.S. commuters. CONCLUSIONS: These results reflect the extent of the air pollution problem in Mexico City. The surrounding topography exacerbates the problems caused by heavy vehicular traffic, poor emission-control devices on older vehicles, and poor maintenance practices. Elevated levels of gasoline components in the blood of nonoccupationally exposed commuters emphasize the need for regulatory initiatives and mass-transit options to reduce hydrocarbon emissions and thus reduce the risk for nonoccupational exposure for the residents of Mexico City. OBJETIVO: Evaluar la exposición a compuestos orgánicos volátiles en usuarios de transporte no expuestos ocupacionalmente en la Ciudad de México. MATERIAL Y MÉTODOS: Se determinaron las concentraciones sanguíneas de benceno, tolueno, etilbenceno, m/p-xileno, o-xileno y metil-terbutil éter en muestras obtenidas de participantes después del traslado matutino. RESULTADOS: Las concentraciones promedio de benceno en sangre (0.11mg/l), etilbenceno (0.081mg/l), m-/p-xileno (0.32mg/l) y tolueno (0.56mg/l) en los participantes de la Ciudad de México son aproximadamente dos veces más elevadas que en la submuestra de no fumadores de la Tercera Encuesta de Nutrición y Salud (Third National Health and Nutrition Examination Survey) en la población de Estados Unidos de América. Por otro lado, la mediana de los niveles de Compuestos Orgánicos Volátiles fueron similares a las medianas observadas en otros estudios de viajeros en ciudades de los Estados Unidos de América, no obstante el hecho de que sólo la mitad de los participantes de la Ciudad de México viajan en vehículos de uso personal, en comparación con los viajeros de los Estados Unidos de América. CONCLUSIONES: Estos resultados reflejan el problema de la contaminación ambiental en la Ciudad de México, donde la topografía que la rodea incrementa los problemas causados por el tráfico vehicular intenso, el bajo control de emisiones en los vehículos viejos y las pobres prácticas de mantenimiento. Los niveles altos de componentes de gasolina en la sangre de los viajeros no expuestos ocupacionalmente enfatizan la necesidad de iniciativas regulatorias y alternativas para disminuir el tráfico que reduzcan las emisiones de hidrocarburos y, en consecuencia, el riesgo de exposición no ocupacional para los residentes de la Ciudad de México.